THE ROLE OF SOCIAL NETWORKS IN HUMAN LIFE TODAY (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
As we live in an age where the Internet is rapidly developing, we must adhere to the culture of using the Internet. The Internet is like a web of a butterfly worm, if it makes a mistake in weaving, it will remain wrapped in its shell, if it continues to weave without making mistaake , it will become a beautiful butterfly.If we also use the Internet to get the useful information we need, we can become good professionals in the future . Therefore, it is necessary to teach the youth to distinguish between white and black, and to understand that they should not fall into the wrong currents and get wrapped up in their shells.